No Evidence of Induced Skin Cancer or Other Skin Abnormalities after Long‐Term (66 week) Chronic Exposure to 222‐nm Far‐UVC Radiation. (8th June 2022) - Welch, David; Kleiman, Norman J.; Arden, Peter C.; Kuryla, Christine L.; Buonanno, Manuela; Ponnaiya, Brian; Wu, Xuefeng; Brenner, David J.
Abstract: Far‐UVC radiation, typically defined as 200–235 nm, has similar or greater anti‐microbial efficacy compared with conventional 254‐nm germicidal radiation. In addition, biophysical considerations of the interaction of far‐UVC with tissue, as well as multiple short‐term safety studies in animal models and humans, suggest that far‐UVC exposure may be safe for skin and eye tissue. Nevertheless, the potential for skin cancer after chronic long‐term exposure to far‐UVC has not been studied. Here, we assessed far‐UVC induced carcinogenic skin changes and other pathological dermal abnormalities in 96 SKH‐1 hairless mice of both sexes that were exposed to average daily dorsal skin doses of 400, 130 or 55 mJ cm −2 of 222 nm far‐UVC radiation for 66 weeks, 5 days per week, 8 h per day, as well as similarly‐treated unexposed controls. No evidence for increased skin cancer, abnormal skin growths or incidental skin pathology findings was observed in the far‐UVC‐exposed mice. In addition, there were no significant changes in morbidity or mortality. The findings from this study support the long‐term safety of long‐term chronic exposure to far‐UVC radiation, and therefore its potential suitability as a practical anti‐microbial approach to reduce airborne viral and bacterial loads in occupied indoor settings. Abstract : We assessed far‐UVC‐induced carcinogenic skin changes and other pathological dermal abnormalities in 96 SKH‐1 hairless mice of both sexes that were exposed to average daily dorsal skin doses of 400 , 130 or 55 mJ cm −2 of 222 nm far‐UVC radiation for 66 weeks, 5 days per week, 8 h per day, as well as similarly treated unexposed controls. No evidence for increased skin cancer, abnormal skin growths or incidental skin pathology findings was observed in the far‐UVC‐exposed mice. The findings from this study support the long‐term safety of long‐term chronic exposure to far‐UVC radiation.